PENGARUH PENGGUNAAN MEDIA ASSEMBLR EDU TERHADAP HASIL BELAJAR SISWA PADA MATERI SIKLUS AIR KELAS V SDN TAMBAAN 1 - Rahmawati Solikin; Ika Dian Rahmawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the effect of using Assembler Edu media on student learning outcomes in the water cycle material of class V SDN Tambaan 1. This study uses a quantitative research type of experimental method with a Pre-Experimental Design design in the form of One-Group Pretest-Posttest Design. The population in this study were all students of class V UPTD SDN Tambaan 1. Sampling used a saturated sampling technique. The research sample consisted of 26 students. Data were collected using observation, tests, and questionnaires. The prerequisite test used was a normality test with the Shapiro Wilk technique, which was then tested with a paired sample t-test to test the hypothesis. The results of the hypothesis test show that the Sig. (2-tailed) value is 0.00 <0.05 so it can be said that HO is rejected and it can be concluded that there is a significant influence on the use of Assemblr Edu media on the water cycle material on the learning outcomes of class V students.